2015
DOI: 10.1111/jace.13708
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐Dependent Scaling Behavior of Dynamic Hysteresis in Pb(Zr,Ti)O3 Ceramics

Abstract: The dynamic hysteresis scaling behaviors of Nb‐doped Pb(Zr0.52Ti0.48)O3 ceramics have been investigated as a function of electric field amplitude (E0) and frequency (f) at different temperatures (T). The loop area of saturated loops is found to follow various power laws as  ∝ E00.3065 at fixed f and  ∝ f 0.0120 at fixed E0. Furthermore, the linear scaling relation  = k3 fαE0β + b3 is estimated under various temperatures. The exponents α (=0.01) and β (=0.10) are T‐independent, whereas the slopes k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Wongdamnern et al found that the α and β values of BaTiO 3 ceramics vary widely when the crystal structures change from tetragonal to orthorhombic and then to rhombohedral . However, Chen et al reported that the scaling relations of rhombohedral, morphotropic, and tetragonal PZT ceramics could take identical α and β values . Our research on (1 − x )Pb(Mg 1/3 Nb 2/3 )O 3 − x PbTiO 3 (PMN‐PT; 0.1 ≤ x ≤ 0.40) ceramics indicates that the α and β values are quite different at the composition of relaxor ferroelectric side ( x ≤ 0.33) from those at the normal ferroelectric side ( x = 0.40) .…”
Section: Scaling Exponents Of Different Ferroelectric Systemsmentioning
confidence: 65%
See 1 more Smart Citation
“…Wongdamnern et al found that the α and β values of BaTiO 3 ceramics vary widely when the crystal structures change from tetragonal to orthorhombic and then to rhombohedral . However, Chen et al reported that the scaling relations of rhombohedral, morphotropic, and tetragonal PZT ceramics could take identical α and β values . Our research on (1 − x )Pb(Mg 1/3 Nb 2/3 )O 3 − x PbTiO 3 (PMN‐PT; 0.1 ≤ x ≤ 0.40) ceramics indicates that the α and β values are quite different at the composition of relaxor ferroelectric side ( x ≤ 0.33) from those at the normal ferroelectric side ( x = 0.40) .…”
Section: Scaling Exponents Of Different Ferroelectric Systemsmentioning
confidence: 65%
“…The scaling behaviors have also been carried out in PbZrO 3 antiferroelectrics, Bi 4 YFeTi 3 O 15 (BYFTO) multiferroics, (K 0.5 Na 0.5 )NbO 3 lead‐free ferroelectrics, and molecular ferroelectric diisopropylammonium bromide . Temperature‐dependent and stress‐dependent scaling behaviors of ferroelectrics were also investigated on some ferroelectric materials . However, few investigations have been done on the dynamic scaling behaviors of oriented ferroelectric thin films or texture ferroelectric ceramics.…”
Section: Scaling Exponents Of Different Ferroelectric Systemsmentioning
confidence: 99%